Effect of environmental pollution on animal and human health: A review - PRABHAKAR, S; SINGH, A K; POONI, D S (The Indian Journal of Animal Sciences, 2012)
Rapid industrialization and development of modern technology are amongst the foremost factors to blame for the general pollution. Livestock sector is one of the several industries that have faced criticism because of its influence on the environment. There is particular concern about the pollution caused by effluents, gases, heavy metals, industrial contaminants and particulate emissions which significantly affect health of both livestock and man. Reciprocally, pollutants from livestock system can affect atmosphere, water and the food chain. However, with rapid population growth there is phenomenal increase in the demand for livestock products, this situation has led to change in the farming system from subsistence farming to commercial and from pastoral livestock systems to more intensive systems of production. Thus, there is a need to address these problems at various levels. The present review has been undertaken to determine the impact of different elements in the environment that cause pollution in animals and human beings as well as pollutants emanating from the intensive livestock production systems and adequate strategies to overcome this problem.